POSSIBILITY SUBSTANTIATION OF A RATIONAL HORIZONTAL STIFFNESS REALIZATION OF THREE-PIECE TRUCK DESIGN - Orlova, A. M. (Science and Transport Progress, 2004)
The paper proposes a general approach to the choice of in-plane stiffness of three-piece bogie including the expressions of shear and bending stiffness and the dependencies of a critical speed on tangent track and in curves, wear factor and lateral acceleration on their values. Mathematical models of elastic and swing types of “side frame – wheelset” connection as well as of the spatial wedge system justify the possibility to achieve reasonable parameters.